1971
DOI: 10.1039/j39710000153
|View full text |Cite
|
Sign up to set email alerts
|

Naturally occurring quinones. Part XVIII. New spinochromes from Diadema antillarum, Spatangus purpureus, and Temnopleurus toreumaticus

Abstract: The spines of Diadema anti//arurn are pigmented with 6-ethyl-2,3,7-trihydroxynaphthazarin and its 2and 3-mOnOmethyl ethers. The test of Temnopleurus toreumaticus contains 3-acetyl-2,6,7-trihydroxyjuglone and six other known spinochromes. and the pigments of Spatanguspurpureus include two common naphthazarins and two novel binaphthaquinones, ethylidene-3,3'-bis(2,6,7-trihydroxynaphthazarin) and its anhydro-derivative. The latter is also present in S. raschi and in Stronglyocentrotus drobachiensis. AB9 2UE, Scot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
37
0

Year Published

1971
1971
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 0 publications
2
37
0
Order By: Relevance
“…Dimethyl ether 3 and monomethyl ethers 4 and 5, which are found in sea urchin shell [5] and are the principal products of partial hydrolysis of 2, were isolated by preparative TLC and characterized by HPLC, PMR, and 13 C NMR. Their physical chemical properties agreed with those reported earlier [4,5].Thus, a technically more suitable method for demethylating 2 by boiling in HBr:AcOH that not only has a higher yield but also uses cheap, nontoxic, and highly soluble biodegradable reagents was found. This enables the reaction to be carried out with lower amounts of reagents and to avoid problems with recycling of synthetic wastes.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Dimethyl ether 3 and monomethyl ethers 4 and 5, which are found in sea urchin shell [5] and are the principal products of partial hydrolysis of 2, were isolated by preparative TLC and characterized by HPLC, PMR, and 13 C NMR. Their physical chemical properties agreed with those reported earlier [4,5].Thus, a technically more suitable method for demethylating 2 by boiling in HBr:AcOH that not only has a higher yield but also uses cheap, nontoxic, and highly soluble biodegradable reagents was found. This enables the reaction to be carried out with lower amounts of reagents and to avoid problems with recycling of synthetic wastes.…”
mentioning
confidence: 99%
“…Dimethyl ether 3 and monomethyl ethers 4 and 5, which are found in sea urchin shell [5] and are the principal products of partial hydrolysis of 2, were isolated by preparative TLC and characterized by HPLC, PMR, and 13 C NMR. Their physical chemical properties agreed with those reported earlier [4,5].…”
mentioning
confidence: 99%
“…Mathieson et al [154] found that the spines of Diademaantillarurn were mainly pigmented with 6-ethyl-2,3,7-trihydroxynaphthazarin ( Figure 3, structure 3) and its 2-and 3-mono-methylethers.…”
Section: Echinochrome and Spinochrome In Sea Urchinsmentioning
confidence: 98%
“…Apparently, more drastic conditions are needed for their formation. 16 The formation of compound 4a can be explained, by all appearances, by ready hydrolysis of the methoxy group at position 2 of aldehyde 2b, that leads to the formation of the benzo[b]xanthenedione product.…”
mentioning
confidence: 99%